A szórvány magyar tanköteles gyermekek családon kívüli elhelyezése Baranyában az 1941–1942-es tanévben - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The framework for the placing of Hungarian compulsory school children outside the family was based on the 25.360/1941. Religion and Public Education Ministerial decree, which constituted new provisions from the 1941/1942 school year for the education of native Hungarian children living in non-Hungarian environment. The reason for issuing the decree was the growing demand of the nationalities for education in their native language, which the Hungarian state – after the failure of the unified education system introduced in 1935 – made available to them in 1941. This measure was supported by nationalities as well, but at the same time we must not forget that the Horthy-era represented a strong national policy, and the patriotic, national education began in elementary school. Thus, the education of Hungarian children could not be neglected while striving to fulfil the needs of nationalities. According to paragraph 1 of the 25.360/1941. Religion and Public Education Ministerial decree on the education of Hungarian children: ‘A native Hungarian compulsory school child living in Hungary, who stays in a not native Hungarian environment must be educated in a Hungarian school or class, by a traveling teacher, in a Hungarian boarding school, or in another native Hungarian environment.’ The placing of children outside the family was only necessary if there was no school with Hungarian educational language in the municipality, because in that case ‘a native Hungarian child living in the municipality (city) can only be sent by his or her tutelary to such a school, until reaching the age of compulsory schooling.’ In accordance with the decree, from the summer of 1941 the Education Inspectorate collected data on the native Hungarian compulsory school children who lived in a non-Hungarian environment to provide them enrolment elsewhere. The first version of the options listed in the decree (Hungarian school or class in municipality) is not the subject of the study, since in that case, the child remains in the family. The second version – a traveling teacher – would not cause change either, but I did not find any example of this in the archives anyway. What may be more interesting in the terms of Family law is the placing in a boarding school or with a family of a relative or acquaintance in native Hungarian environment - this is indicated by the phrase in an otherwise ‘native Hungarian environment’. I give examples of these cases – boarding school and placement in Hungarian families – from practice based on archival records.